Do car-mounted mobile measurements used for radio-frequency spectrum regulation have an application for exposure assessments in epidemiological studies?. (January 2016) - Bolte, John F.B.; Maslanyj, Myron; Addison, Darren; Mee, Terry; Kamer, Jos; Colussi, Loek
Abstract: Knowing the spatial and temporal trends in environmental exposure to radiofrequency electromagnetic fields is important in studies investigating whether there are associated health effects on humans and ecological effects on plants and animals. The main objective of this study is to assess whether the RFeye car-mounted mobile measurement system used for radio frequency spectrum monitoring in The Netherlands and the United Kingdom could be of value in assessing exposure over large areas as an alternative to measuring exposure with personal exposure meters or using complex modelling techniques. We evaluated the responses of various body-worn personal exposure meters in comparison with the mobile measurement system for spectrum monitoring. The comparison was restricted to downlink mobile communication in the GSM900 and GSM1800 frequency bands. Repeated measurements were performed in three areas in Cambridge, United Kingdom and in three areas in Amersfoort, The Netherlands. We found that exposure assessments through the car-mounted measurements are at least of similar quality to exposure modelling and better than the body worn exposimeter data due to the absence of the shielding effect. The main conclusion is that the mobile measurements provide an efficient and low cost alternative particularly in mapping large areas. Highlights: Car mounted measurements of radiofrequency electromagnetic fields is possible. Re-using car-mounted ether regulation measurements in epidemiology is possible. Car-mounted measurements are at least of similar quality to exposure modelling. Car-mounted measurements are of better quality to body worn exposimeter data.